Risk assessment of Listeria monocytogenes in ready-to-eat foods : interpretative summary (WHO, 2004)
Listeria monocytogenes is widely dispersed in the environment and foods and is capable of growing even at refrigeration temperatures. Foodborne listeriosis although relatively rare is a clinically serious disease with a high case-fatality rate that largely affects specific higher-risk segments of the population. Cases of listeriosis appear to be predominately associated with ready-to-eat products. FAO and WHO have undertaken a risk assessment to addresses the risk of listeriosis associated with these foods and specific risk management questions posed by the Codex Committee on Food Hygiene (CCFH) This volume provides a summary of that risk assessment. The interpretative summary includes an overview of the risk assessment with a particular focus on information that would be relevant to risk managers faced with addressing problems posed by this pathogen in ready-to-eat foods. It includes answers to the specific risk management questions posed by the CCFH and outlines the issues to be considered when implementing control measures including the establishment of microbiological criteria. This volume and others in this Microbiological Risk Assessment Series contain information that is useful to both risk assessors and risk managers the Codex Alimentarius Commission governments and food regulatory agencies industries and other people or institutions with an interest in the area of Listeria monocytogenes its impact of public health and food trade and the use microbiological risk assessment in its control.
Microbiological risk assessment series, ISSN 1726-5274 no. 4
Keywords: hodnocení rizik; bakteriologie; Listeria monocytogenes; Listeriosis; listeriové infekce; zemědělství a potravinářství; Food Contamination; mikrobiologie, lékařská mikrobiologie; kontaminace potravin; Food Handling; Risk Assessment; manipulace s potravinami; Bacteriology